Musculoskeletal Health Conditions Represent a Global Threat to Healthy Aging: A Report for the 2015 World Health Organization World Report on Ageing and Health - Briggs, Andrew; Cross, M.; Hoy, D.; Sànchez-Riera, L.; Blyth, F.; Woolf, A.; March, L. (Gerontological Society of America, 2016)
Persistent pain, impaired mobility and function, and reduced quality of life and mental well-being are the most common experiences associated with musculoskeletal conditions, of which there are more than 150 types. The prevalence and impact of musculoskeletal conditions increase with aging. A profound burden of musculoskeletal disease exists in developed and developing nations. Notably, this burden far exceeds service capacity. Population growth, aging, and sedentary lifestyles, particularly in developing countries, will create a crisis for population health that requires a multisystem response with musculoskeletal health services as a critical component. Globally, there is an emphasis on maintaining an active lifestyle to reduce the impacts of obesity, cardiovascular conditions, cancer, osteoporosis, and diabetes in older people. Painful musculoskeletal conditions, however, profoundly limit the ability of people to make these lifestyle changes. A strong relationship exists between painful musculoskeletal conditions and a reduced capacity to engage in physical activity resulting in functional decline, frailty, reduced well-being, and loss of independence. Multilevel strategies and approaches to care that adopt a whole person approach are needed to address the impact of impaired musculoskeletal health and its sequelae. Effective strategies are available to address the impact of musculoskeletal conditions; some are of low cost (e.g., primary care-based interventions) but others are expensive and, as such, are usually only feasible for developed nations. In developing nations, it is crucial that any reform or development initiatives, including research, must adhere to the principles of development effectiveness to avoid doing harm to the health systems in these settings.